University and labor field: women in the field of communication - Hernández Vélez, Adrián; Montiel Meléndez, Michel (IE Revista de Investigación Educativa de la REDIECH, 2021)
From the perspective of professional careers, we approach the incursion of women in the field of communication in the state of Tlaxcala (Mexico). The research had epistemic support of a hermeneutic-phenomenological type and the methodological architecture corresponded to a case study. Among the findings, three profiles were identified: pioneers, with a consolidated career and new ones. Also, a mutual foundation relationship was found between the community of communication experts and the Universidad del Altiplano, which was established as the first private higher education institution and bastion in the training of graduates with this professional profile.